Decision Support System for Selecting Inventory Applications Using the WASPAS and Rank Sum Methods - Tungga Bhimadi Karyasa; Rhaishudin Jafar Rumandan; Nurhayati Nurhayati; Yani Sugiyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Inventory applications can help companies monitor, manage, and optimize their inventory. However, the large number of existing inventory applications makes it difficult for companies that want to use inventory applications to choose the right application. This is because to choose an inventory application that suits the company's needs, you have to know each application one by one, so it takes a long time and is difficult to make a choice. This research aims to develop a decision support system for selecting inventory applications by applying the WASPAS (Weighted Aggregated Sum Product Assessment) and Rank Sum approaches. The WASPAS method is used to combine the weights for each criterion and calculate the assessment results based on the product of the criteria values with the appropriate weights. Meanwhile, the Rank Sum weighting technique is used to assign weights or rankings to a number of elements or objects based on their level of importance. Based on the case studies that have been carried out, the results obtained for each alternative include: Zoho Inventory (A4) obtained a value of 0.8531; Onstok (A3) obtained a value of 0.8310; Sortly: Inventory Simplified (A2) obtained a value of 0.7735; BoxHero-Inventory Management (A5) obtained a value of 0.7680; and Shelfit-Inventory Management (A2) obtained a value of 0.6613. In usability testing, we got an average score of 91%, and we can say that the system is suitable for use.